2007
DOI: 10.1530/eje-07-0099
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Ki-67 and prognostic factors for recurrence/progression of gonadotropic adenomas after first surgery

Abstract: Objective: Gonadotropin-secreting pituitary adenomas carry a high risk of local recurrence or progression (R/P) of remnant tumor after first surgery. The clinical characteristics and the long-term outcome of these silent adenomas, which show no signs of endocrine hyperfunction, differ from those of other types of pituitary adenomas. However, to date, no study has focused specifically on gonadotropic adenomas. Materials and methods: To identify prognostic factors of R/P of remnants, we studied the postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
3
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 50 publications
1
41
3
7
Order By: Relevance
“…20) Some studies also demonstrated a correlation between MIB-1 labeling index and re-growth or recurrence, 9,14,30,32) but other studies found no such correlations. 5,13,24,27) These discrepancies and differences between estimates of the threshold MIB-1 labeling index may be attributable to variations in the definition of recurrence or progression. 26) Another possible source of differences or discrepancies is the method used to count the labeled cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20) Some studies also demonstrated a correlation between MIB-1 labeling index and re-growth or recurrence, 9,14,30,32) but other studies found no such correlations. 5,13,24,27) These discrepancies and differences between estimates of the threshold MIB-1 labeling index may be attributable to variations in the definition of recurrence or progression. 26) Another possible source of differences or discrepancies is the method used to count the labeled cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some other studies did not show any significant correlation between MIB-1 index and CS invasion. 1,5,14,22,28,33) Whether invasive potential affects progression remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein expression of Ki-67 was examined by immunohistochemical staining in 91 invasive pituitary tumors. The Ki-67 labeling index (LI) was calculated as the ratio of the labeled over total nuclear areas (Dubois et al 2007). …”
Section: Immunohistochemistrymentioning
confidence: 99%
“…However, several studies did not confirm the correlation of these criteria with clinical behavior and aggressiveness of each individual adenoma (4,5,6,7,8,9,10). In particular, the Ki-67 LI, widely used to determine cellular growth fraction in many types of tumors, is accepted as prognostic indicator in pituitary tumors, although controversial results have emerged from clinical studies and criticisms are also reported in the literature (6,11,12,13,14,15).…”
Section: Introductionmentioning
confidence: 99%